Right kind of wrong : the science of failing well - Edmondson, Amy C. (Atria Books, 2023)
"Award-winning Harvard Business School professor Amy Edmondson has influenced legion MBA grads as well as Big Think authors from Brené Brown to Adam Grant with her pioneering work on psychological safety. Now, Amy is bringing her work to the wider world, upending our entire cultural notion of failure with this guide to the science of failing well, which actualizes the potential of psychological safety for both individuals and organizations alike"--